2023
DOI: 10.2147/ijn.s386560
|View full text |Cite
|
Sign up to set email alerts
|

Formulation for the Targeted Delivery of a Vaccine Strain of Oncolytic Measles Virus (OMV) in Hyaluronic Acid Coated Thiolated Chitosan as a Green Nanoformulation for the Treatment of Prostate Cancer: A Viro-Immunotherapeutic Approach

Abstract: Background: Oncolytic viruses are reported as dynamite against cancer treatment nowadays. Methodology: In the present work, a live attenuated oral measles vaccine (OMV) strain was used to formulate a polymeric surfacefunctionalized ligand-based nanoformulation (NF). OMV (half dose: not less than 500 TCID units; 0.25 mL) was encapsulated in thiolated chitosan and outermost coating with hyaluronic acid by ionic gelation method characterizing parameters was performed. Results and Discussion: CD44 high expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 39 publications
2
19
0
Order By: Relevance
“…Morphological and physiochemical characterization of HA-ThCs-NDV revealed that the nanoparticle size was 290.4nm, zeta potential was 22.3 mV with 0.265 PDI. These results are in accordance with our earlier study that reported NP size of 275.6 mm, ± 11.5mV zeta potential and PDI = 0.372 for targeted delivery of oncolytic measles virus loaded into polymeric thiolated chitosan nanoparticles and targeted against CD44 receptors in prostate cancer cells ( 36 ). Another study reported encapsulation of NDV in chitosan nanoparticles with particle size of 371nm and a zeta potential of +2.84 mV ( 37 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Morphological and physiochemical characterization of HA-ThCs-NDV revealed that the nanoparticle size was 290.4nm, zeta potential was 22.3 mV with 0.265 PDI. These results are in accordance with our earlier study that reported NP size of 275.6 mm, ± 11.5mV zeta potential and PDI = 0.372 for targeted delivery of oncolytic measles virus loaded into polymeric thiolated chitosan nanoparticles and targeted against CD44 receptors in prostate cancer cells ( 36 ). Another study reported encapsulation of NDV in chitosan nanoparticles with particle size of 371nm and a zeta potential of +2.84 mV ( 37 ).…”
Section: Discussionsupporting
confidence: 93%
“…These findings suggest that CD44 receptor mediated uptake of HA-ThCs-NDV produced a greater oncolytic effect in HeLa cells as compared to naked NDV virus. Another study reported similar high cytopathic effect of HA functionalized thiolated chitosan encapsulated oncolytic measles virus against prostate cancer cells with IC 50 of 5.1 and 3.52 for pure measles and NPs loaded NDV ( 36 ).…”
Section: Discussionmentioning
confidence: 76%
“…Regardless of the different routes of administration for therapeutic moieties, the particle size and shape have a protruding influence on the transport rate and diffusion mechanism of nanoparticles inside the cell matrix.
Figure 5 SEM images ( A : upper) show spherical and smooth surfaces of nanoparticles of Empty HA-ThCs and ( B : upper) HA-coated 5-FU in ThCs-NPs at the scale of 5.0um while the TEM images ( A : lower) showed more precise images of spherical and smooth surfaces of Empty HA-ThCs and ( B : lower) HA-coated 5-FU in ThCs-NPs at scale of 50 nm and 200 nm 23 , 24 , 35 .
…”
Section: Results and Interpretationsmentioning
confidence: 99%
“…Measuring drug content in the solution surrounding the nanoparticles indirectly reflects the amount of drug incorporated within the nanoparticles. This method was employed to quantify the amount of 5-FU loaded into the nanoparticles by ionic gelation method and to determine the encapsulation efficiency of these formulations 35 . The nanoparticle formulation was centrifuged at 13,700 rpm for 1 h to perform this analysis.…”
Section: Methodsmentioning
confidence: 99%
“…These hydroxyls are also able to chelate metal ions and, thus, hamper the metal-catalyzed generation of reactive oxygen substances (ROS) and their oxidant activity. According to our research of the literature, the flavonoids that have been included in HA-coated delivery nanosystems investigated against cancer in the last 5 years are the two flavonols: kaempferol [34] and quercetin (QU) [35][36][37][38][39][40][41], the flavanol epigallocatechin-3-gallate (EGCG) [42][43][44][45][46][47] the flavanone naringenin [48], the isoflavone formononetin [49], and a mix of anthocyanins extracted from corn [50]. Between brackets are reported the number of compounds belonging to each class or subclass according to this classification.…”
Section: Phecs Included In Drug Nanodelivery Systems For Tumor Targetingmentioning
confidence: 99%